2020
DOI: 10.1093/occmed/kqaa007
|View full text |Cite
|
Sign up to set email alerts
|

Public Safety Personnel’s interpretations of potentially traumatic events

Abstract: Background Many public safety personnel (PSP) experience trauma directly or indirectly in their occupational role, yet there remain barriers to accessing care or seeking help. Aims To understand how PSP interpret different potentially traumatic events and how perceived eligibility for being traumatized is determined among PSP. Methods We analysed open-ended c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The results are generally consistent with previous results for correctional workers from the current sample ( 6 , 14 , 16 , 28 ). The current paper provides novel and important results indicating significant and substantial differences between correctional officers and wellness services employees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results are generally consistent with previous results for correctional workers from the current sample ( 6 , 14 , 16 , 28 ). The current paper provides novel and important results indicating significant and substantial differences between correctional officers and wellness services employees.…”
Section: Discussionsupporting
confidence: 92%
“…The nature, severity, and frequency of PPTE exposures, as well as occupation type and occupational stressors, have all been associated with diverse rates of PTSD ( 2 , 6 , 15 ). In a recent study, the most common event identified by communications officials, correctional workers, paramedics, and police officers as being the worst event they had ever experienced was sudden violent death ( 6 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such work can affect all those working in correctional services, beyond those who appear to work in direct and frequent contact with prisoners. Correctional services workers employed in institutional, community, or administrative roles share experiences of either direct (e.g., witnessing, intervening in incidents) or indirect (e.g., report reading) exposures to potentially psychologically traumatic events ( Perez et al, 2010 ; Bierie, 2012a ; Carleton et al, 2019 ; Ricciardelli and Power, 2020 ; Ricciardelli et al, 2020 ). Despite variation in the degree of exposure, experiencing potentially psychologically traumatic events in whatever form appears associated with an increased risk of screening positive for a mental disorder ( Carleton et al, 2018a , b ; Ricciardelli et al, 2018a , b ).…”
Section: Current Studymentioning
confidence: 99%
“…Relative to the general population, public safety personnel (PSP) [e.g., border services officers, public safety communications officials, correctional workers, firefighters (career and volunteer), Indigenous emergency managers, operational intelligence personnel, paramedics, police] [ 1 , 2 ] appear at increased risk for compromised physical [ 3 ], psychological [ 4 ], and emotional [ 5 ] well-being. The increased risk PSP experience is due, at least in part, to potentially psychologically traumatic event (PPTE) [ 2 ] exposures [ 6 , 7 ]. PPTEs refer to actual or threatened incidents of compromised physical, sexual, and mental well-being (e.g., acts of violence, fires, accidents resulting in fatalities, and explosions) [ 1 , 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPTEs refer to actual or threatened incidents of compromised physical, sexual, and mental well-being (e.g., acts of violence, fires, accidents resulting in fatalities, and explosions) [ 1 , 6 , 8 , 9 ]. Exposure to one or more PPTEs is common (i.e., 89.7%) in the general population [ 10 ]; however, most PSP report repeated exposures (i.e., more than 11 exposures over their lives) to diverse types of PPTE, with some PSP reporting more exposures than they can count [ 6 , 7 ]. Carleton et al [ 4 , 11 ] highlighted that PSP report symptoms consistent with various mental health disorders at higher rates than expected for the general population.…”
Section: Introductionmentioning
confidence: 99%